PENGARUH KETERAMPILAN CLUSTERING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 4 SUTERA KABUPATEN PESISISR SELATAN - Maimukminis, Seni One; Edriati, Sofia; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACT This research is caused students low understanding of mathematical concepts are. Because in learning process is still focus on the teacher . The students still have low ability to explore their idea and to arrange the material . So, one of way to solve this problem is by appliying the ability of Clustering .The goal of this research is to know the influence of clustering toward students understanding of mathematics concepts at grade nine SMPN 4 sutera. Metodology research used experimental research. By using type One Shot Case Study. The population of this research is all grade nine students of SMPN 4 Sutera. In collecting the data by using Sampling simple random sampling, the graden nine (IX2) as experimental class. The final tests is analized by using simple regretion analyze. Thus, the research found the coofesien of corelation r = 0,49. It means the ability of clustering sampling has influence toward students of understanding of mathematics concepts at grade nine student of SMPN 4 Sutera.